Differences of Age and Gender Related Posture in Urban and Rural Schoolchildren Aged 7 to 10 - Vilma Dudonienė; Rasa Šakalienė; Ligija Švedienė; Inga Musteikytė Petrauskienė (Lithuanian Sports University, 2018)
Research  background  and  hypothesis.  Postural  disorders  appear  to  be  one  of  the  biggest  health  threats  in Lithuania. Especially significant alterations in children's health-related behaviour emerge when they start going to school. These changes in their daily routine are often faulty and may lead to the deteriorating health condition. Postural abnormalities need to be corrected as early as possible before they become permanent. According to some authors, rural children are more physically active compared to city children, therefore it is interesting to identify is there is any difference in body posture in rural and urban schoolchildren. Research aim was to assess and compare posture in urban and rural schoolchildren aged 7 to 10. Research sample: 248 schoolchildren (109 - from urban area; 139 - from rural area). Research  methods.  Posture  of  rural  and  urban  schoolchildren  was  assessed  using W.  K.  Hoeger's  method. Alignment of ten body segments was visually evaluated in a frontal (head, shoulders, spine, hips, knees and ankles) and sagittal (neck and upper back, trunk, abdomen, lower back, legs) planes. Research  results.  There  were  no  significant  differences  (p   >  0.05)  in  total  posture  score  between  girls (41.80 ± 6.87) and boys (40.62 ± 7.13). Girls and boys from the rural area had significantly (p  < 0.05) higher total posture score than their counterparts from the urban area. Discussion and conclusions. There were no significant differences in total posture score between girls and boys. Regardless of age and gender, schoolchildren from rural area had better posture than children from urban area. Keywords: alignment of body segments, area of residence, children's posture.